Management of Laryngoscope-Induced Iatrogenic Dental Injury: A Case Series - Mridula Goswami; Vashi Narula; Ramanandvignesh Pandiyan (Bulletin of Emergency and Trauma)
Dental injury is a common anesthesia-related adverse event, with a high incidence of damage to teeth and surrounding tissues during oro-endotracheal intubation. Poor oral hygiene, compromised periodontium, faulty or loose prosthesis, proclined maxillary incisors along with increased difficulty level of airway management, improper use of laryngoscope, and use of maxillary anterior teeth as a fulcrum for achieving accessibility to the airway are all risk factors for iatrogenic dental injury. This type of injury provides additional physical and psychological trauma to patients who have already undergone medical surgical procedures. The consequences of such mishaps might potentially result in medico-legal suits and financial claims.The present case series described three cases of managing iatrogenic dental lesions during oro-endotracheal intubation, after obtaining written informed consent, as well as methods for preventing such accidental injuries. This study emphasized the importance of collaboration between medical and dental professionals in preventing and successfully managing accidental dental injuries.